Based on the equation you provided earlier and the options available, let's fill in the blanks step by step. The original equation is:
\[ 5x - 12 - 6x = -10x + 7 - 1 \]
On simplifying, we derived:
- Combine like terms:
- On the left side: \(5x - 6x - 12 = -x - 12\)
- On the right side: \(-10x + 7 - 1 = -10x + 6\)
So we have:
\[ -x - 12 = -10x + 6 \]
Now, let's follow through the correct option sequence based on simplifications.
-
Combine like terms:
This doesn't match any options. Let's reframe this step using the options provided.
-
Use the option assigning to combine terms:
- Using the option: 1x - 12 = -10x + 6
Which is the combined left and right from our earlier calculation.
-
Now, isolate x:
- We can rearrange to:
\[ 1x + 10x = 6 + 12 \]
- Which gives:
\[ 11x = 18 \]
- This combined scenario should have a representation of 9x - 12 = 6 to gain continuity.
-
Continuing from \(9x - 12 = 6\), add \(12\):
-
Divide by 9:
None of the provided options directly match the calculations (as they typically start with simplifying or reorganizing parts).
Additional possible options from what was derived:
- \(9x - 12 = 6\)
- \(x = 2\)
If you're looking to fill the blanks directly, the likely option choices would align to extract through:
- Combine \(1x - 12 = -10x + 6\)
- Apply remains, \(-12 = -10x + 6\)
- Gathering, subsequently realizing views across \(-12 + 12 = −10x + 6 + 12\) helps showcase if iterative expressions are consistent.
The end solution remains \(x = 2\) unless clarified for targeting specific segments within presented options.